Clinical Features and Prevalence of Spondyloarthritis in a Cohort of Italian Patients Presenting with Acute Nongranulomatous Anterior Uveitis. (18th January 2022) - Bolletta, Elena; Macchioni, Pierluigi; Citriniti, Giorgia; Mastrofilippo, Valentina; Aldigeri, Raffaella; De Simone, Luca; Gozzi, Fabrizio; Adani, Chantal; Sangiovanni, Anna; Posarelli, Chiara; Figus, Michele; Muratore, Francesco; et al.
Abstract : Purpose . To describe the clinical features of acute nongranulomatous anterior uveitis (NGAU) patients and to estimate the prevalence of concomitant spondyloarthritis (SpA). Methods . Retrospective study of consecutive patients affected by NGAU referred to the Ocular Immunology Unit of the AUSL-IRCCS di Reggio Emilia, Italy, between January 2016 and January 2019. All patients underwent ophthalmic evaluation and blood test with HLA-B27 typing and were referred to a rheumatologist to identify any undiagnosed SpA. SpA was classified according to the Assessment of SpondyloArthritis international Society (ASAS) criteria in axial or peripheral SpA. Patients were divided into two groups: NGAU with associated SpA (SpA+) and NGAU without SpA (SpA-). Clinical and demographic features of the two groups, including sex, HLA-B27, family history of rheumatic disease, uveitis laterality, course, and severity of ocular inflammation, complications, and treatment, were compared. Results . Ninety-nine patients with NGAU were enrolled, of whom 36 (36%) with a diagnosis of SpA: 14 with peripheral SpA and 22 with axial SpA. The prevalence of SpA was higher in HLA-B27-positive patients than in HLA-B27-negative patients (50% vs. 15%, p < 0.0001 ). The multivariate logistic regression (R 2 = 0.28 ) for SpA diagnosis identified as significant predictive factors: age at diagnosis (odds   ratio   OR = 0.95, 95% confidence interval [CI]: 0.91-0.99) and HLA-B27+ (OR = 5.32, 95% CI: 1.80-15.70). Conclusions . Our results confirmed the high prevalence of undiagnosed SpA in patients with NGAU, suggesting that, regardless of HLA-B27 status, in the presence of IBP and/or peripheral arthritis, patients with NGAU must be referred to the rheumatologist to allow earlier diagnosis.